GrACE: Grid Adaptive Computational Engine for Parallel Structured AMR Applications - Parashar, Manish; Li, Xiaolin (Advanced Computational Infrastructures for Parallel and Distributed Adaptive Applications, 2009)
This chapter contains sections titled: Introduction Structured Adaptive Mesh Refinement The GrACE Architecture Design and Implementation Of GrACE Partitioning and Runtime Management Algorithms Applications of GrACE Related Work Conclusion Acknowledgments References